Synchrotron Imaging and Modeling of Gel Polymer Electrolyte Transport in Hierarchical Carbon Aerogels for Supercapacitors - Mashkour,M; Singh,M; Hellström,G; Ljung,A-L; Forsberg,F; Lycksam,H; Huber,JAJ; Lundström,TS; Bismarck,A; Oksman,K (ACS Applied Energy Materials, 2026)
Abstract Hierarchically porous carbon aerogels offer significant potential for next-generation energy storage, yet controlling their structure and electrolyte infiltration remains a key challenge. Here, we develop fully biobased carbon aerogels (CAs) derived from a lignin-cellulose nanocrystal blend via ice-templating and carbonization. The resulting anisotropic hierarchical porous structures are infused with poly(vinyl alcohol)-potassium hydroxide gel polymer electrolyte to form semi-solid composite electrodes. Time-resolved synchrotron X-ray microtomography enables direct visualization of structural evolution during carbonization and three-dimensional electrolyte infiltration. Image-based pore-scale modeling performed directly on reconstructed synchrotron X-ray tomographic volumes reveals how the real hierarchical pore network governs gel electrolyte distribution, accessible porosity, and ion transport pathways. The results show that aligned and interconnected pore networks enable deep, uniform electrolyte penetration, reduce transport tortuosity, and increase electrochemically active volume. The structure-transport-performance relationship is validated by electrochemical testing of symmetric supercapacitors, demonstrating stable capacitance and reduced internal resistance. This work establishes a concept for renewable porous carbon electrodes and introduces a scalable CA-gel electrolyte system for high-performance solid-state energy storage.